2023
DOI: 10.1111/epi.17751
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the concept of drug‐resistant epilepsy: A TASK1 report of the ILAE/AES Joint Translational Task Force

Stéphane Auvin,
Aristea S. Galanopoulou,
Solomon L. Moshé
et al.

Abstract: Despite progress in the development of anti‐seizure medications (ASMs), one third of people with epilepsy have drug‐resistant epilepsy (DRE). The working definition of DRE, proposed by the International League Against Epilepsy (ILAE) in 2010, helped identify individuals who might benefit from presurgical evaluation early on. As the incidence of DRE remains high, the TASK1 workgroup on DRE of the ILAE/American Epilepsy Society (AES) Joint Translational Task Force discussed the heterogeneity and complexity of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 164 publications
0
3
0
Order By: Relevance
“…The examples chosen for this commentary relate to the medical treatment of epilepsy, the most common severe chronic neurological condition worldwide, which is characterized by spontaneous recurrent seizures (SRSs) and cognitive and behavioral comorbidities. About one-third of people with epilepsy have DRE in which chronic treatment with ASMs fails to control their seizures ( Auvin et al, 2023 ). Mechanisms of DRE are only incompletely understood but in recent years various animal models of DRE have been created, and it is hoped that these models will provide insights into the mechanisms of pharmacoresistance and allow treatments that overcome drug nonresponding to be identified ( Löscher et al, 2020 ; Löscher and White, 2023 ).…”
Section: Inter-individual Variability Of the Brain’s Response To Drug...mentioning
confidence: 99%
See 1 more Smart Citation
“…The examples chosen for this commentary relate to the medical treatment of epilepsy, the most common severe chronic neurological condition worldwide, which is characterized by spontaneous recurrent seizures (SRSs) and cognitive and behavioral comorbidities. About one-third of people with epilepsy have DRE in which chronic treatment with ASMs fails to control their seizures ( Auvin et al, 2023 ). Mechanisms of DRE are only incompletely understood but in recent years various animal models of DRE have been created, and it is hoped that these models will provide insights into the mechanisms of pharmacoresistance and allow treatments that overcome drug nonresponding to be identified ( Löscher et al, 2020 ; Löscher and White, 2023 ).…”
Section: Inter-individual Variability Of the Brain’s Response To Drug...mentioning
confidence: 99%
“…2 A ). In clinical studies, it has been found that patients with high baseline seizure frequencies are more difficult to treat than those with low seizure frequency ( Auvin et al, 2023 ), which has led to the “intrinsic severity hypothesis” of pharmacoresistance that posits that subjects presenting with high seizure rates have more severe forms of epilepsy and that the increased severity renders them more difficult to treat ( Rogawski, 2013 ). Thus, for the data illustrated in Figure 2 B , a subgroup analysis was performed to assess whether the well-recognized clinical observation regarding treatment responsiveness in individuals with low and high baseline seizure frequencies applies in the rat study.…”
Section: Inter-individual Variability Of the Brain’s Response To Drug...mentioning
confidence: 99%
“…To the Editors, In the article entitled, "Revisiting the Concept of Drug-Resistant Epilepsy: A TASK1 Report of the ILAE/AES Joint Translational Task Force," 1 the authors proposed that "it is necessary to revisit the current definition of DRE, in order to transform the preclinical and clinical research of mechanisms and biomarkers, to identify novel, effective, precise, pharmacologic treatments, allowing for earlier recognition of drug resistance and individualized therapies." 1 The International League Against Epilepsy (ILAE) provided a definition for drug-resistant epilepsy (DRE) more than a decade ago: "failure of adequate trials of two tolerated, appropriately chosen and used antiepileptic drug schedules (whether as monotherapies or in combination) to achieve sustained seizure freedom." 2 The ILAE itself recognized that "Ideally, the evidence should be derived from large-scale, prospective, long-term, population-based studies including both adults and children."…”
Section: Drug Resistance In Epilepsy: a Reappraisal Of The Definition...mentioning
confidence: 99%
“… 8 Despite advantageous, one‐third of patients with epilepsy are unresponsive to ASMs or other treatments resulting in drug‐resistant epilepsy. 9 , 10 The incidence of drug‐resistant epilepsy reported by a meta‐analysis study in 2021 was 13.7% (95% CI: 9.2–19.0) in population/community‐based populations and 36.3% (95% CI: 30.4–42.4) in the clinic‐based cohorts. 11 Drug‐resistant epilepsy and patients who are unable to obtain sustained seizure freedom after a trial of two ASMs may require combination therapy for effective disease management.…”
Section: Introductionmentioning
confidence: 99%